Near-infrared (NIR) absorbing films based on diimmonium dye and cyanine dye for high-performance NIR cut-off filter. (November 2022) - Kim, Hong Mo; Lee, Hyun Kyu; Kim, Suhyeon; Kim, Jae Pil
Abstract: In the CMOS (complementary metal-oxide-semiconductor) image sensor, the NIR cut-off filter is an important component to adjust the image quality by transmitting visible light and blocking near-infrared (NIR) light selectively. In this work, we developed NIR absorbing films applicable to NIR cut-off filter using anti-reflective coatings. A variety of polymeric binders were applied to NIR absorbing films to optimize the thermal stability to the process of anti-reflective coatings. The thermal stability of NIR absorbing films was improved by applying polysulfone (PSU) with high thermal stability. Furthermore, the simultaneous use of a diimmonium dye and a cyanine dye was evaluated to maximize the NIR cut-off ability of the filter. The effect of anti-reflective coatings of TiO2 /SiO2 on both sides of the NIR absorbing films was investigated by the optical simulation. As a result, the NIR cut-off filter based on PSU films incorporating a diimmonium dye and a cyanine dye showed a superior NIR cut-off ability without incident angle dependence and leakage of incident light. Highlights: The NIR absorbing films applying diimmonium and cyanine dyes showed high NIR blocking ability. The NIR absorbing film based on PSU showed high thermal stability for the process of antireflective coatings. The simultaneous use of DB-TFSI and IR-813 was effective to improve the NIR blocking ability of NIR cut-off filter. The NIR cut-off filter applying NIR film exhibited excellent performance without noise problem.